2013
DOI: 10.1039/c3cc39191d
|View full text |Cite
|
Sign up to set email alerts
|

Green scalable aerosol synthesis of porous metal–organic frameworks

Abstract: Benchmarked micro or nanosized HKUST-1, ZIF-8 and Fe3(BTC)2 as well as template-assisted Fe3(BTC)2 metal-organic frameworks (MOFs) of various morphologies were synthesized via a green and scalable aerosol route. Their high space time yields make this continuous method very promising for the industrial production and shaping of MOFs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(36 citation statements)
references
References 30 publications
0
30
1
Order By: Relevance
“…These synthesismethods do not provide arational and universal way of preparing LnMOF nanothermometers, in particular,they are not amenable to scaling-up. Ar ecent collaboration between the groups of Rocha and Carlos, and Maspoch, provided an answer to this challenge by resorting to spray-drying synthesis, extending the methodf rom transition metals [51,52] to lanthanides. [29] In the spray-drying synthesis, the reaction mediumi sa tomized into droplets and Ln-MOFsn anoparticles form during the drying process and self-assemble into superstructures within the droplets, which act as individual reactors confining the growth of the crystals ( Figure 5).…”
Section: Synthesis Methods and Films Processingmentioning
confidence: 99%
“…These synthesismethods do not provide arational and universal way of preparing LnMOF nanothermometers, in particular,they are not amenable to scaling-up. Ar ecent collaboration between the groups of Rocha and Carlos, and Maspoch, provided an answer to this challenge by resorting to spray-drying synthesis, extending the methodf rom transition metals [51,52] to lanthanides. [29] In the spray-drying synthesis, the reaction mediumi sa tomized into droplets and Ln-MOFsn anoparticles form during the drying process and self-assemble into superstructures within the droplets, which act as individual reactors confining the growth of the crystals ( Figure 5).…”
Section: Synthesis Methods and Films Processingmentioning
confidence: 99%
“…Schoenecker et al [78] in 2013 reported a continuous process for the synthesis of UiO-66 using their patented reactor that uses batch technology with an integrated flow system to allow for the removal of products and introduction of reagents in situ. The Serre research group described a scalable aerosol system, which uses two liquid reagent streams injected into a flow of hot air, for the synthesis of HKUST-1, ZIF-8 and Fe 3 (BTC) 2 [79]. A similar spray-drying technique was also demonstrated by Carné-Sánchez et al [80].…”
Section: (D) Metalsmentioning
confidence: 99%
“…One solution to the problems encountered in liquid/liquid MOF synthesis is to perform self‐assembly at liquid/air interfaces generated in an aerosol, as one can use the same mixtures as those used in solvothermal synthesis 43. 44 In fact, our group has synthesised a wide range of hollow MOF superstructures by exploiting the special conditions that dictate precipitation and reaction during the drying of an aerosol droplet (see Figure 6 f). 43 This spray‐drying method does not require any additional immiscible solvents, surfactants, emulsifiers or agitation (e.g., stirring or sonication).…”
Section: Self‐assembly Using Soft Templatesmentioning
confidence: 99%